Numerical Study on the Characteristics of Hydrogen Leakage, Diffusion and Ventilation in Ships - Chang-Yong Lee; Sang-Kyun Park (Energies)
Hydrogen is a promising environmentally friendly fuel with the potential for zero-carbon emissions, particularly in maritime applications. However, owing to its wide flammability range (4–75%), significant safety concerns persist. In confined spaces, hydrogen leaks can lead to explosions, posing a risk to both lives and assets. This study conducts a numerical analysis to investigate hydrogen flow within hydrogen storage rooms aboard ships, with the goal of developing efficient ventilation strategies. Through simulations performed using ANSYS-CFX, this research evaluates hydrogen diffusion, stratification, and ventilation performance. A vertex angle of 120° at the ceiling demonstrated superior ventilation efficiency compared to that at 177°, while air inlets positioned on side-wall floors or mid-sections proved more effective than those located near the ceiling. The most efficient ventilation occurred at a velocity of 1.82 m/s, achieving 20 air exchanges per hour. These findings provide valuable insights for the design of safer hydrogen vessel operations.